ANALISIS YURIDIS TERHADAP PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR: 425 K/AG/2014 TENTANG CERAI GUGAT - Muhibbuthabary, Muhibbuthabary (Universitas Islam Negeri Raden Intan Lampung, 2015)
Abstract: Juridical Analysis on the Decision of Supreme Court of Republic of Indonesia Number: 425 K/Ag/2014 Concerning Divorce Suit. A Court ruling is a statement declared by judge in a court of law, aiming to end or to settle a lawsuit/disputes between parties. Every decision of the Court should contain the principle of justice, benefit, and legal certainty. This paper attempts to analyze the Supreme Court Decision No. 425 K/AG/2014 concerning divorce, from the aspect of material and procedural law. The results showed that the decision has fulfilled the above-three elements, on account of : (1) from the material aspect, the decision clearly included and considered all the requests of the parties, and did not violate the provisions of material law on divorce. (2) from the formal aspect, the decision was in accordance with the provisions of article 184 paragraph 1 of H.I.R, Article 178 of H.I.R and Article 189 of R.Bg.Abstrak: Analisis Yuridis Terhadap Putusan Mahkamah Agung Republik Indonesia Nomor: 425 K/Ag/2014 tentang Cerai Gugat. Putusan pengadilan adalah suatu pernyataan hakim yang diucapkan di muka persidangan dengan tujuan untuk mengakhiri atau menyelesaikan suatu perkara/sengketa. Setiap putusan Pengadilan harus mengandung nilai keadilan, nilai kemanfaatan, dan nilai kepastian hukum. Tulisan ini mencoba menganalisis putusan Hakim Nomor: 425 K/AG/2014 tentang cerai gugat, ditinjau dari aspek hukum materil dan hukum formil. Hasil penelitian menunjukkan bahwa putusan tersebut telah memenuhi ketiga unsur di atas, karena : (1) dari aspek materil, putusan ini secara jelas telah mencantumkan dasar permohonan, mempertimbangkan semua tuntutan para pihak, dan tidak menyalahi ketentuan hukum materil tentang percerain; (2) dari aspek formal, putusan ini